The Role of Learning Satisfaction in Mediating Influence on Interpersonal Communication, Self-Efficacy, and Motivation Readiness Work at the Faculty of Economics Students, Bhayangkara University, Surabaya - Enny Istanti; Sumiati Sumiati; Riyadi Nugroho; Achmad Daengs GS (Journal of Managerial Sciences and Studies, 2025)
This study examines the role of learning satisfaction in mediating the influence of interpersonal communication, self-efficacy, and motivation on work readiness among students of the Faculty of Economics, Bhayangkara University Surabaya. The research addresses the challenge of how higher education institutions can better prepare graduates for the labor market by identifying the psychological and behavioral factors that shape employability. A quantitative research design was applied using a survey method. Data were collected from 210 students through a structured questionnaire, and the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypothesized relationships. The results indicate that interpersonal communication, self-efficacy, and motivation positively influence learning satisfaction and work readiness. However, learning satisfaction does not significantly mediate the relationship between these predictors and work readiness. These findings suggest that while satisfaction with learning contributes to employability outcomes, it is not the sole mechanism through which personal and interpersonal factors affect work readiness. Additional experiential and contextual factors, such as internships, soft skills development, and practical exposure, may play a stronger role.This study contributes to the literature by providing empirical evidence from the Indonesian higher education context, highlighting the limited mediating role of learning satisfaction. Practically, the findings underscore the importance for universities to enhance not only the quality of learning experiences but also to integrate work-based learning and career development programs to strengthen students' readiness for the workplace.